Porous Lattice Structure Optimization in 3D Printed Insole Design (Journal of Fiber Bioengineering and Informatics, 2025)
This work realises the total parametric design of the insole through the topological structural designof the lattice units, which helps to meet the pressure requirements of different locations and increasethe comfort and personalisation of insoles. Prior research has primarily concentrated on creating planarporous structures and basic geometric insole structures; intricate three-dimensional lattice structureoptimisation has been systematically neglected. To close this gap, the research examines three commonporous lattice structural units for analysis: equilateral triangular, square, and hexagonal units. It doesthis by using 3D printing technology to produce customised insoles. In addition, variance analysis iscarried out, and the orthogonal experimental design method is used to examine the significant impact ofstructural design factors on the compressive performance of the porous lattice structure. The lattice’sstructural neutral size, unit size, and rod diameter are chosen to influence the elastic modulus. Witha 22% reduction in maximum plantar pressure and an 18% reduction in average pressure compared tothe uniform solid structure, research reveals a considerable improvement in plantar pressure distributionwith the lattice insole structure created in this study. In the meantime, the porous lattice structure’soverall weight is 15% less than that of the solid structure, which successfully reduces the insole’s burdenwhile still fulfilling the standards for mechanical performance. This study offers a fresh technologicalperspective on creating customised, comfortable insoles.